SEBUAH TANGGAPAN ATAS EMPAT DOKUMEN YANG DIKELUARKAN DAN DISAHKAN OLEH KONFERENSI WALI GEREJA INDONESIA TENTANG PEMBARUAN KARISMATIK KATOLIK INDONESIA - Simanullang, Gonti (UNIKA Santo Thomas, 2013)
The Indonesian bishops have issued four documents in which they state their pastoral responses to the Indonesian Catholic Charismatic Renewal (CCR). The 1993 Various Charisms, One Spirit, addressed to all Catholics of Indonesia, gives significant attention to CCR Service Committees at various levels and briefly the term ‘baptism in the Holy Spirit’. The 1995 The Renewal of Christian Lifewas a revision of the 1983 Pastoral Guidelines,is particularly addressed to Indonesian CCR and speaks of issues among which are ‘baptism in the Holy Spirit’, praying in tongues, and Service Committees. These 1993 and 1995 documents will be reviewed since they speak, although briefly, about the issue of ‘baptism in the Holy Spirit’. This article is a critical comment on the documents and recommends their need for revision.